2003
DOI: 10.1093/annonc/mdg097
|View full text |Cite
|
Sign up to set email alerts
|

Idoxifene versus tamoxifen: a randomized comparison in postmenopausal patients with metastatic breast cancer

Abstract: Idoxifene was both active and well tolerated in postmenopausal women with metastatic breast cancer. Idoxifene had similar efficacy and toxicity to tamoxifen in this randomized comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Tamoxifen was first approved in 1977 by the U.S. FDA for the treatment of metastatic breast cancer and breast cancer. Other triphenylethylene SERMs, analogs of tamoxifen, have been studied for breast cancer prevention and/or treatment, including droloxifene (3-hydroxytamoxifen) [269][270][271], idoxifene (pyrrolidino-4-iodotamoxifen) [272][273][274][275], and ospemifene [276].…”
Section: Tamoxifenmentioning
confidence: 99%
“…Tamoxifen was first approved in 1977 by the U.S. FDA for the treatment of metastatic breast cancer and breast cancer. Other triphenylethylene SERMs, analogs of tamoxifen, have been studied for breast cancer prevention and/or treatment, including droloxifene (3-hydroxytamoxifen) [269][270][271], idoxifene (pyrrolidino-4-iodotamoxifen) [272][273][274][275], and ospemifene [276].…”
Section: Tamoxifenmentioning
confidence: 99%
“…Morbidity was similar for both groups. The authors concluded that in postmenopausal women with metastatic breast cancer, idoxifene had similar efficacy and toxicity compared to TAM [115]. Idoxifene has not been developed further because of concerns about uterine prolapse.…”
Section: Idoxifenementioning
confidence: 99%
“…53 Idoxifene is metabolically more stable through the substitution of iodine at the 4-position of TAM and showed comparable efficacy and safety profiles as TAM, but caused the side effect of uterine prolapse and was hence stopped from further development. 54 The phosphate miproxifene, was also proven inferior to TAM and was thus canceled from further development. 55 Nafoxidine and its saturated form lasofoxifene are fixed ring analogs of OHT, whereby the isomerization to the cis-isomer is prohibited.…”
Section: Comparisons Of Selected Sermsmentioning
confidence: 99%